Concrete’s Furthest North. Early 20th Century Heritage of Modern Civil Engineering in Iceland - Ármannsson, Pétur H. (Docomomo International, 2011)
In 1935–36, the English writer and design critic Philip Morton Shand (1888-1960), proponent of Modernism, translator of Walter Gropius and founder of MARS group (Modern Architectural Research Group) published two articles in the magazine “The Concrete Way”. The first one was entitled “Concrete´s furthest north”, highlighting the advanced and wide–ranging use of concrete construction in Iceland. With the second article were photographs of newly built public buildings by architect Sigurdur Gudmundsson (1885-1958) as well as bridges designed in the 1920s and 1930s by the engineers of the Icelandic State Highways Department. Shand was impressed by the work of the “gifted and thoroughly modern minded architect such as any country might be proud of” as well as the work of “first rate–engineers” of this “geographically remote island which at that time had only 100,000 inhabitants and 2,000 motorcars. He also points at the photos "as evidence of the wonderful clearness of the air which is characteristic of Iceland´s brief Arctic summers."